Crystal face engineering optimization and electrochemical performance improvement of NiCo2Se4 electrode material

By introducing defects into NiCo2Se4 electrode materials and optimizing their crystal surface engineering, the problems of low conductivity and insufficient electrochemical activity are solved, and its electrochemical performance is significantly improved, which is suitable for high-performance supercapacitors.

CN119542035AInactive Publication Date: 2025-02-28LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411649687.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The low conductivity and poor electrochemical activity of NiCo2Se4 electrode materials seriously affect its electrochemical properties, limiting its application in supercapacitors.

Method used

By introducing defects on the atomic scale, the NaBH4 treatment method is used to control the Se vacancy defect concentration, and the crystal surface engineering of NiCo2Se4 electrode material is optimized to improve its electrochemical performance.

Benefits of technology

The electrochemical performance of the electrode material is significantly improved through defect engineering, the current density, integral area and specific capacity are improved, the cycle life is extended, and the energy storage density and kinetic performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542035A_ABST
    Figure CN119542035A_ABST
Patent Text Reader

Abstract

The invention provides crystal face engineering optimization and electrochemical performance improvement of a NiCo2Se4 electrode material, and belongs to the technical field of energy storage materials.The energy storage performance of the material.By finely adjusting Se vacancy defect concentration, the energy storage performance of the material.Firstly, a high-uniformity NiCo precursor is prepared through a hydrothermal method, high-quality Va-NiCo2Sex is synthesized through the follow-up Se step, and the high-quality Va-NiCo2Sex is prepared; the method is characterized in that a defect regulation and control strategy is introduced, generation of Se vacancies is accurately controlled under different concentrations, a series of Va-NiCo2Sex (a is 0.5-2.5 mol) defect samples with adjustable defect concentration are obtained, the electrode structure regulation and control capability is remarkably enhanced, the structural integrity and morphology optimization of the material are ensured through advanced characterization such as XRD, SEM and TEM, an optimized active substance is adopted for electrode preparation, and the preparation process is simple and convenient. According to the preparation method, a nickel foam current collector is mixed with polyvinylidene fluoride (PVDF) and polyvinylidene fluoride (NMP) binders, the nickel foam current collector is coated with the mixture, an efficient electrode structure is formed, and maximization of electrode performance is achieved through precisely-controlled coating and pressing processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy storage materials, and specifically relates to crystal surface engineering optimization of NiCo2Se4 electrode materials and improvement of their electrochemical performance. Background Art

[0002] With the rapid development of high-tech around the world, the new energy industry, emerging electronics industry, clean energy and other fields are changing with each passing day. The demand for energy storage devices with higher energy storage density and smaller size is increasing. Supercapacitors are a promising energy storage device. NiCo2Se4, as a typical pseudocapacitor material, has attracted considerable attention in the field of supercapacitor energy storage materials due to its valence diversity and high electrochemical activity. However, low conductivity and poor electrochemical activity seriously affect the electrochemical performance of NiCo2Se4, restricting its practical application. Our team intends to introduce defects at the atomic scale, hoping to maximize the electrochemical performance of electrode materials by systematically exploring the relationship between Se vacancy concentration and its electrochemical performance. Studies have shown that the effects of different vacancy defect concentrations are completely different. Therefore, obtaining the parameters that control the vacancy defect concentration is particularly important for improving the electrochemical performance of electrode materials. At the same time, it is hoped that the above conclusions can provide a theoretical basis for constructing high-performance energy storage devices with high energy and power density, long cycle life, low production cost and green environmental protection-pseudocapacitor supercapacitors.

[0003] Based on this, in the preparation of NiCo2Se with different defect concentrations x When preparing the material, it is proposed to use NaBH4 treatment instead of hydrogen reduction annealing. This method makes it easier to control the number and type of Se defects, simplifies the process flow while improving the purity of the defective material, and further improves the preparation efficiency. It is expected that through systematic exploration, the optimal parameters for controlling the concentration of vacancy defects in NiCo2Se4 defective materials can be obtained, and high-performance devices with high specific capacity, good rate performance and long-term cycle stability can be further constructed. This is of great significance for the development of efficient, high-performance and low-cost energy storage materials, and can promote the development of energy storage technology, which will help solve the energy storage problems faced by the new energy field, improve energy utilization efficiency, and reduce energy consumption costs, which will play a positive role in promoting economic development.

[0004] Therefore, based on the above technical problems, it is necessary to design the crystal surface engineering optimization of NiCo2Se4 electrode materials and improve their electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0005] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0006] Figure 1 It is a linear cyclic voltammetry analysis diagram of the present invention; Summary of the invention

[0007] The purpose of the present invention is to provide crystal surface engineering optimization of NiCo2Se4 electrode materials and improvement of their electrochemical performance, aiming to solve the problem of defects in electrochemical performance, especially lattice distortion. Although this defect affects the surrounding atoms, the ingenious regulation of defect engineering can improve the electrode structure and electrical properties of the material, and significantly improve the electrochemical performance. In the study, NiCo2Se4 uses different vacancies to regulate, ingeniously introduce disorder and electronic chaos, expand the diversity of metal element valence states, activate more electrochemical reaction sites, strengthen the redox kinetic process, greatly improve the energy storage density of supercapacitors, and realize high-efficiency devices. In summary, the defect engineering strategy effectively regulates the electronic structure, chemical properties or conductivity of the material, thereby further optimizing the electrochemical performance of the material, solving the problems of lattice defects and electrochemical performance. NiCo2Se4 improves electrochemical performance and strengthens energy storage problems through regulation.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] Crystal surface engineering optimization of NiCo2Se4 electrode material and improvement of its electrochemical performance, and its preparation method comprises the following steps:

[0010] S1. First, the step of synthesizing NiCo precursor involves 1.74g Co(NO3)2·6H2O and 0.87g Ni(NO3)2·6H2O, which are dissolved in 60ml deionized water and stirred thoroughly. After stirring, they are transferred to a 100ml stainless steel autoclave and reacted at 120°C for 12 hours. After that, they are naturally cooled to room temperature. The product is washed by centrifugation with deionized water and ethanol several times, and dried in a vacuum oven at 60°C overnight. The final powder needs to be ground and sintered in air at 350°C for 4h to stabilize the structure and morphology.

[0011] S2, the preparation stage of NiCo2Se4 main material, this step involves fully mixing 3g NaOH and 0.4g Se powder with 35ml deionized water, then adding 0.14g NiCo precursor prepared in advance and stirring continuously until completely dissolved, placing the mixture into a stainless steel high-pressure reactor, and conducting a deep reaction at 200°C for 16h. After the reaction is completed, the product is ensured to be pure through careful precipitation collection, repeated washing with deionized water and ethanol. Finally, the washed sample is air-dried at 60°C overnight, and then advanced analysis techniques such as XRD, SEM and TEM are used to accurately characterize key parameters such as its crystal structure, morphology and size, laying the foundation for electrochemical performance testing;

[0012] S3. To further improve the performance, 80 mg NiCo2Se4 powder was suspended in 40 ml deionized water, and different concentrations of NaBH4 solution (ranging from 0.5 mol to 2.5 mol) were added step by step. The reaction was carried out at 100 °C for 6 h to form NiCo2Se4 with different defect concentrations. x After thorough cleaning, ethanol treatment and vacuum drying at 60°C, these specially treated materials were labeled V 0.5 -NiCo2Se x ,V1-NiCo2Se x ,V 1.5 -NiCo2Se x ,V2-NiCo2Se x and V 2.5 -NiCo2Se x .

[0013] As a preferred solution of the present invention, its preparation method also includes: S4, optimized Va-NiCo2Sex, mixed with polyvinylidene fluoride (PVDF) and n-methylpyrrolidone (NMP) in a specific mass ratio, and then adding N-CH3C4H7NO and 1-CH3-2-C4H7NO solvents to obtain a uniform slurry, and the slurry is evenly coated on a 1cm×1cm nickel foam substrate, and vacuum dried and cured for 12h to ensure that the electrode material loading is about 2mg. Finally, the electrode is pressed and formed at a pressure of 10MPa to prepare for electrochemical testing.

[0014] S5. As a preferred solution of the present invention, cyclic voltammetry was used to test, using 3MKOH as the electrolyte, setting a NiCo2Se4 electrode and an electrode containing specific defects (such as V 0.5 -NiCo2Se x To V 2.5 -NiCo2Se x ) were working electrodes, AgCl was the reference electrode, and Pt was the counter electrode. -1 The test was carried out at a scan rate of , and the experimental results clearly showed that the electrode containing defects showed higher current density and integrated area than the unoptimized NiCo2Se4 electrode, which directly reflected its enhanced specific capacity, and strongly proved that the electrochemical performance of the electrode material has been significantly improved through crystal surface engineering optimization and defect regulation strategy.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] 1. In this scheme, by introducing the NiCo2Se4 regulation strategy, the generation of Se vacancies is precisely controlled at different concentrations, and a series of NiCo2Se4 with different defect concentrations are prepared. x Samples, this process not only achieved precise control of material defects at the atomic scale, but also significantly improved the electrode structure through defect engineering, increased active sites, and promoted the effective transfer of electrons. These defective materials showed higher current density and integrated area than the unoptimized NiCo2Se4, which directly demonstrated their enhanced specific capacity and electrochemical activity, laying a solid foundation for the improvement of energy storage performance.

[0017] 2. In this scheme, the optimized electrode preparation process not only focuses on the regulation of the active material itself, but also involves the overall optimization of the electrode structure. By mixing with polyvinylidene fluoride (PVDF) and polyvinylidene fluoride (NMP) binders and using specific solvents, a uniform slurry is prepared and coated on a nickel foam substrate. The optimization of the electrode structure is ensured through precise coating, drying and pressing processes. Such an electrode design not only enhances the conductivity, but also ensures a good loading of the active material and improves the electrochemical performance of the overall electrode. The cyclic voltammetry test shows that the defective electrode treated in this way has better performance than the traditional electrode, verifying the effectiveness of the structural optimization.

[0018] 3. In this scheme, this scheme not only solves the limitations of NiCo2Se4 electrode materials, but also provides new ideas for the design of electrode materials for a wider range of electrochemical energy storage systems such as supercapacitors and lithium-sulfur batteries. Through defect regulation strategies, the energy storage efficiency and kinetic performance of the materials are improved, while the structural stability is optimized, which is conducive to extending the cycle life. This is crucial for the pursuit of new energy applications with high-efficiency and long-life energy storage devices. In addition, the flexibility and effectiveness of this strategy encourage further research and development of high-performance, low-cost energy storage materials, which has far-reaching significance for promoting the development of energy storage technology, improving energy utilization, reducing energy consumption costs, and promoting economic sustainable development. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1

[0021] Please refer to the attached Figure 1 , the present invention provides the following technical solutions:

[0022] Crystal surface engineering optimization of NiCo2Se4 electrode material and improvement of its electrochemical performance, and its preparation method comprises the following steps:

[0023] S1. First, the step of synthesizing NiCo precursor involves 1.74g Co(NO3)2·6H2O and 0.87g Ni(NO3)2·6H2O, which are dissolved in 60ml deionized water and stirred thoroughly. After stirring, they are transferred to a 100ml stainless steel autoclave and reacted at 120°C for 12 hours. After that, they are naturally cooled to room temperature. The product is washed by centrifugation with deionized water and ethanol several times, and dried in a vacuum oven at 60°C overnight. The final powder needs to be ground and sintered in air at 350°C for 4h to stabilize the structure and morphology.

[0024] S2, the preparation stage of NiCo2Se4 main material, this step involves fully mixing 3g NaOH and 0.4g Se powder with 35ml deionized water, then adding 0.14g NiCo precursor prepared in advance and stirring continuously until completely dissolved, placing the mixture into a stainless steel high-pressure reactor, and conducting a deep reaction at 200°C for 16h. After the reaction is completed, the product is ensured to be pure through careful precipitation collection, repeated washing with deionized water and ethanol. Finally, the washed sample is air-dried at 60°C overnight, and then advanced analysis techniques such as XRD, SEM and TEM are used to accurately characterize key parameters such as its crystal structure, morphology and size, laying the foundation for electrochemical performance testing;

[0025] S3. To further improve the performance, 80 mg NiCo2Se4 powder was suspended in 40 ml deionized water, and different concentrations of NaBH4 solution (ranging from 0.5 mol to 2.5 mol) were added step by step. The reaction was carried out at 100 °C for 6 h to form NiCo2Se4 with different defect concentrations. x After thorough cleaning, ethanol treatment and vacuum drying at 60°C, these specially treated materials were labeled V 0.5 -NiCo2Se x ,V1-NiCo2Se x ,V 1.5 -NiCo2Se x ,V2-NiCo2Se x and V 2.5 -NiCo2Se x .

[0026] In this embodiment: S1 stage: NiCo precursor preparation: In this stage, the NiCo precursor is prepared by a precisely controlled hydrothermal synthesis method to ensure the uniform distribution of Ni and Co elements. Co(NO3)2·6H2O, Ni(NO3)2·6H2O and urea are used as initial raw materials in the preparation process, and the reaction is carried out under specific conditions. The precursor is carefully cleaned, dried and sintered at high temperature, which not only promotes the orderly growth of the crystal, but also strengthens the stability of the structure, providing a good prerequisite for the next step of Se process;

[0027] S2 stage: vacancy defect regulation and performance optimization:

[0028] In the third stage, different concentrations of NaBH4 were introduced to adjust V a -The concentration of Se vacancy defects in NiCo2Se4 is the core innovation of this technical solution. By changing the concentration of Se in NiCo2Se4, the formation of Se can be precisely controlled, and then the electrode structure of the material can be adjusted, which is a key factor affecting the electrochemical performance. x The solution resulted in the formation of a series of V 0.5 -NiCo2Se x To V 2.5 -NiCo2Se x Each sample represents a unique electrode structure state, providing an experimental sample for studying the relationship between vacancy concentration and electrochemical performance indicators such as capacitance, energy density, and rate capability;

[0029] Electrochemical performance evaluation: Next, these samples with different vacancy concentrations are subjected to detailed electrochemical performance tests, including cyclic voltammetry, galvanic charge-discharge, etc., to evaluate their specific capacitance, cycle stability, and rate performance. By comparing the performance of each sample, the specific influence of vacancy concentration on electrochemical performance can be clarified, providing data support for optimizing the design of energy storage devices;

[0030] Combining theory and experiment: In order to gain a deeper understanding of the impact of vacancy defects on electrode structure and electron transport mechanism, theoretical methods such as first-principles calculations can be combined with experimental results to establish a microscopic mechanism model for performance improvement;

[0031] Practical application exploration: In view of the demand for high-efficiency and long-life energy storage devices in the new energy field, the optimized V a-NiCo2Se4 material is expected to show excellent performance in supercapacitors and lithium-sulfur batteries, especially in wind and solar energy storage systems. Its high energy storage density and excellent kinetic performance can effectively alleviate the challenges faced by current energy storage technology; analyze material preparation; prepare NiCo precursor by hydrothermal method, drive the preparation of NiCo2Se4, and then react with NaOH, Se powder and NaBH4 solution to obtain NiCo2Se with different vacancy concentrations x Defective materials;

[0032] Electrochemical performance characterization, including electrochemical performance testing:

[0033] Cyclic voltammetry test: Cyclic voltammetry test determines the energy storage mechanism of nanomaterials by the shape of the curve. When a symmetrical rectangular shape is shown, it represents the typical double-layer capacitance behavior; and the presence of a pair of redox peaks indicates the presence of pseudocapacitance. In addition, the cyclic voltammetry test process also plays a role in activating electrode materials. The commonly used scan rate range is 2 to 50mv per second.

[0034] Cross-current charge and discharge test: The cross-current charge and discharge test is to charge and discharge the system by setting a cross-current current to analyze the electrochemical reaction process, and calculate the capacity, energy density and rate of the electrode material according to the charge and discharge curve. The calculation formula of the specific capacity is based on the discharge current density, voltage window size and area under the discharge curve;

[0035] In view of the application expansion of supercapacitor electrode materials in the field of lithium-sulfur batteries, the study paid special attention to defect regulation technology, especially by adjusting the optimal vacancy concentration parameters to transfer this technology to lithium-sulfur battery technology. Due to the poor electronic conductivity and ionic conductivity of elemental sulfur, the conductivity of sulfur materials at room temperature is extremely low, which is not conducive to the high-rate performance of the battery. Secondly, sulfur and lithium sulfide have a volume expansion or contraction of up to 79% during the charging and discharging process. This expansion will cause changes in the morphology and structure of the positive electrode, resulting in the separation of sulfur from the conductive skeleton, thereby causing capacity decay; this volume effect will be amplified in large batteries, resulting in significant capacity decay, which may cause battery damage, and huge volume changes will destroy the electrode structure. This work hopes to use electrode materials with different defect concentrations to composite and assemble lithium-sulfur batteries, and by testing the electrochemical properties of the battery, explore the changes in its electrochemical properties, aiming to provide new strategies and directions for the rational composite design of lithium-sulfur battery electrode materials.

[0036] The structural and morphological characterization of materials includes the following methods:

[0037] EDS and energy dispersive spectroscopy: EDS is used to observe the morphology and surface structure at the micro-nano scale, while energy dispersive spectroscopy can perform qualitative and quantitative analysis of the elements in the sample area. EDS can be used to compare the microscopic morphology changes before and after vacancy defect treatment, and combined with EDS to analyze the differences in element content:

[0038] TEM: TEM can provide high-resolution images (about 0.1 to 0.2 nm) for observing the ultrastructure of materials, including particle size, lattice constant and internal crystal structure, and is helpful for analyzing lattice defects:

[0039] Raman: Raman is a non-destructive detection method that can determine the surface structure and crystal phase changes of materials, especially the identification of defects, by analyzing the characteristic peaks generated by the interaction between light and chemical bonds in materials:

[0040] XPS photoelectron spectroscopy: By measuring the energy of photoelectrons excited by XPS, the type, content and chemical state of elements on the sample surface can be determined, which helps to understand the composition changes of the material before and after the introduction of defects and provides information for a deeper understanding of defect engineering;

[0041] For details, please refer to S4. The optimized Va-NiCo2Sex was mixed with polyvinylidene fluoride (PVDF) and n-methylpyrrolidone (NMP) in a specific mass ratio, and then N-CH3C4H7NO and 1-CH3-2-C4H7NO solvents were added to prepare a uniform slurry. The slurry was evenly coated on a 1cm×1cm nickel foam substrate and cured by vacuum drying for 12h to ensure that the electrode material loading was about 2mg. Finally, the electrode was pressed under a pressure of 10MPa to prepare for electrochemical testing.

[0042] In this embodiment: In summary, the research on the crystal surface engineering optimization of NiCo2Se4 electrode materials and the improvement of their electrochemical performance has demonstrated several key steps and innovations through a sophisticated preparation process and performance testing:

[0043] Active material optimization: Through the S1-S3 steps, the synthesis of NiCo2Se4 material and NiCo2Se x Precise regulation of vacancy defects is the basis for improving electrode performance, because defect engineering can increase active sites and promote the transport of electrons and ions;

[0044] Refined processing of electrode preparation: The preparation of electrodes not only considers the selection and ratio of active materials, but also carries out detailed control in the processes of slurry preparation, coating, drying and pressing, ensuring the optimization of the electrode's electrical conductivity, mechanical strength and active material loading;

[0045] Comprehensive evaluation of electrochemical performance: Through cyclic voltammetry, galvanostatic charge and discharge tests, not only the basic performance of the electrode is evaluated, but also the long-term cycle stability and performance under specific conditions are studied in depth, providing detailed data support for the practical application of the material;

[0046] Performance improvement and mechanism analysis: Defect regulation significantly improves the specific capacity and electrochemical activity of the electrode, and improves the energy storage efficiency and kinetic performance by enhancing the transmission of electrons and ions. It also optimizes the structural stability and extends the cycle life of the battery.

[0047] For details, please refer to S5. Cyclic voltammetry was used to test the NiCo2Se4 electrode and the electrode with specific defects (such as V0.5-NiCo2Se x To V2.5-NiCo2Se x ) were used as working electrodes, AgCl was used as reference electrode, and Pt sheet was used as counter electrode. The tests were carried out at a scanning rate of 50 mV s-1. The experimental results clearly showed that the electrode containing defects exhibited higher current density and integrated area than the unoptimized NiCo2Se4 electrode, which directly reflected its enhanced specific capacity. This strongly proved that the electrochemical performance of the electrode material has been significantly improved through crystal surface engineering optimization and defect regulation strategy.

[0048] In this embodiment: the electrolyte: a 3M KOH solution is selected, which is suitable for electrochemical energy storage systems such as supercapacitors, can effectively promote ion transmission, and is beneficial to electrochemical reactions;

[0049] Test system: A standard three-electrode system was constructed, with NiCo2Se4 electrode and electrode containing specific defects (such as V 0.5 -NiCo2Se x To V 2.5 -NiCo2Se x ) were working electrodes, AgCl was used as reference electrode, and Pt sheet was used as counter electrode, which were taken as the research objects to ensure the reliability and reproducibility of the test;

[0050] Test parameters: 50ms -1 The CV test was performed at a scan rate of , which is suitable for capturing the fast response of the electrode while not missing the slow reaction process;

[0051] Test results and analysis:

[0052] Performance improvement: The results show that compared with the unoptimized NiCo2Se4, the defective electrode (V 0.5 -NiCo2Se x To V 2.5 -NiCo2Sex ) shows that the current density is larger and the integrated area is wider. The increased current density indicates faster electron transfer and enhanced charge storage capacity, and the increased integrated area directly reflects the increase in specific capacity;

[0053] Subsequent research directions:

[0054] Deepening of mechanistic understanding: Through theoretical calculations, such as density functional theory, we explore how defects change the material electrode structure and reveal the root cause of performance enhancement;

[0055] Long-term stability: In addition to CV, long-term cycle life tests are conducted to evaluate the performance of defective electrodes after multiple charge and discharge tests to ensure durability in practical applications;

[0056] Process optimization: Based on test feedback, adjust defect concentration and electrode preparation parameters to find the best combination;

[0057] Practical verification: Select the electrode material to make a prototype, conduct actual measurement verification, such as supercapacitor or hybrid energy storage application, and evaluate the actual performance;

[0058] Electrochemical performance test

[0059] In the electrochemical performance test, the V containing Se vacancies obtained by precise control a -NiCo2Se x The defective electrode material is composited with a high conductivity material in order to obtain a composite electrode material with excellent electrical conductivity. Subsequently, the composite material is tightly and evenly coated on a nickel foam substrate to form an electrode. After being assembled into a supercapacitor unit, a detailed electrochemical performance evaluation will be carried out with the help of an advanced electrochemical workstation. The linear cyclic voltammetry test will reveal the capacitive properties of the electrode, including double-layer capacitance and pseudocapacitive behavior, as well as the reversibility of the reaction. By testing at different scan rates, the rate performance of the material can be evaluated, that is, the capacity retention ability under rapid charge and discharge conditions. In addition, the transverse current charge and discharge test will be used to determine the specific capacity and energy density of the electrode. By analyzing the charge and discharge curves, the charge and discharge behavior and cycle stability of the material can be further understood. These test data will be systematically summarized and analyzed to deeply understand how defect engineering affects the electrochemical behavior of NiCo2Se4 materials.

[0060] As for the study of the mechanism of the influence of defects on the electrochemical properties of NiCo2Se4 materials, the calculation work using density functional theory is an important tool for understanding material properties at the atomic scale. First, the basic structure of NiCo2Se4 is optimized through theoretical calculations to ensure the accuracy of the model. This step is the cornerstone of subsequent calculations. Then, based on the element ratio information given by the energy scattering spectrum in the experiment, a Se atom in the NiCo2Se4 electrode structure is simulated and a vacancy model is created to simulate the defect state in the actual material. This defect model allows in-depth exploration of how vacancies change the electrode structure of the material, especially focusing on how vacancies affect NiCoSe4's OH - The adsorption capacity of OH - The adsorption of vacancies is closely related to electrochemical reactions and is one of the key factors determining the performance of pseudocapacitors. By calculating the electronic state of materials at different vacancy concentrations, we can further infer the direct impact of vacancies on charge storage capacity, charge transfer kinetics, and electrochemical reaction pathways, thereby revealing how defect regulation strategies optimize the energy storage performance of electrode materials. The combination of these theoretical analyses and experimental data provides an in-depth physical picture to guide the design and optimization of high-performance energy storage materials.

[0061] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be deemed to be a reasonable choice.

Claims

1. Crystal surface engineering optimization of NiCo2Se4 electrode material and improvement of its electrochemical performance, the preparation method thereof comprises the following steps: S1. First, the step of synthesizing NiCo precursor involves 1.74g Co(NO3)2·6H2O and 0.87g Ni(NO3)2·6H2O, which are dissolved in 60ml deionized water and stirred thoroughly. After stirring, they are transferred to a 100ml stainless steel autoclave and reacted at 120°C for 12 hours. After that, they are naturally cooled to room temperature. The product is washed by centrifugation with deionized water and ethanol several times, and dried in a vacuum oven at 60°C overnight. The final powder needs to be ground and sintered in air at 350°C for 4h to stabilize the structure and morphology. S2, the preparation stage of NiCo2Se4 main material, this step involves fully mixing 3g NaOH and 0.4g Se powder with 35ml deionized water, then adding 0.14g NiCo precursor prepared in advance and stirring continuously until completely dissolved, placing the mixture into a stainless steel high-pressure reactor, and conducting a deep reaction at 200°C for 16h. After the reaction is completed, the product is ensured to be pure through careful precipitation collection, repeated washing with deionized water and ethanol. Finally, the washed sample is air-dried at 60°C overnight, and then advanced analysis techniques such as XRD, SEM and TEM are used to accurately characterize key parameters such as its crystal structure, morphology and size, laying the foundation for electrochemical performance testing; S3. To further improve the performance, 80 mg NiCo2Se4 powder was suspended in 40 ml deionized water, and different concentrations of NaBH4 solution (ranging from 0.5 mol to 2.5 mol) were added step by step. The reaction was carried out at 100 °C for 6 h to form V with different defect concentrations. a -NiCo2Se x After thorough cleaning, ethanol treatment and vacuum drying at 60°C, these specially treated materials were labeled V 0.5 -NiCo2Se x ,V1-NiCo2Se x ,V 1.5 -NiCo2Se x ,V2-NiCo2Se x and V 2.5 -NiCo2Se x .

2. According to claim 1, the crystal surface engineering optimization and electrochemical performance improvement of the NiCo2Se4 electrode material, the preparation method thereof further comprises: S4. The optimized Va-NiCo2Sex was mixed with polyvinylidene fluoride (PVDF) and n-methylpyrrolidone (NMP) in a specific mass ratio, and then N-CH3C4H7NO and 1-CH3-2-C4H7NO solvents were added to prepare a uniform slurry. The slurry was evenly coated on a 1cm×1cm nickel foam substrate and cured by vacuum drying for 12h to ensure that the electrode material loading was about 2mg. Finally, the electrode was pressed under a pressure of 10MPa to prepare for electrochemical testing.

3. The crystal surface engineering optimization and electrochemical performance improvement of the NiCo2Se4 electrode material according to claim 2, wherein the testing method comprises: S5. Cyclic voltammetry was used to test the NiCo2Se4 electrode and the electrode with specific defects (such as V0.5-NiCo2Sex to V2.5-NiCo2Sex) as the working electrodes, respectively. AgCl was used as the reference electrode and Pt sheet was used as the counter electrode. The test was performed at a scan rate of 50 mV s-1. The experimental results clearly showed that the electrode with defects exhibited higher current density and integrated area than the unoptimized NiCo2Se4 electrode, which directly reflected its enhanced specific capacity. This strongly proved that the electrochemical performance of the electrode material has been significantly improved through crystal surface engineering optimization and defect regulation strategies.